2022
DOI: 10.14740/gr1509
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Predictors of Non-Alcoholic Fatty Liver Disease in a Retrospective Cohort of Patients With Crohn’s Disease

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) is an emerging extraintestinal manifestation (EIM) of Crohn’s disease (CD). We aimed to investigate the prevalence and comorbid predictors of NAFLD in patients with CD. Methods We conducted a nationwide retrospective cohort study to determine the prevalence, characteristics, comorbidities, and hospitalization outcomes associated with NAFLD in patients with CD. Comparison between groups was performed by Mann-Whitney te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…The second study reported an adjusted OR of 259; 95% CI: −787 to 1306, P = 0.627 [25,26]. However, Abomhya et al (215 049 patients) demonstrated an increase in median total hospitalization costs of 32 305.5 USD; IQR = 18 600-61 599 in NAFLD+IBD patients vs. 30 782 USD; IQR = 16 847-58 667, P < 0.001 for those with IBD alone [18]. Noorian et al also showed increased cost of care (COC) in patients with IBD and NAFLD ranging from 7223 to 7634 USD; 95% CI: 923-17 116, P < 0.01 in CD (18 170 patients) and 8358 to 9392 USD; 95% CI: 3200-14 662, P < 0.01 in UC patients (9866 patients) [19].…”
Section: Hospitalization Costmentioning
confidence: 93%
See 3 more Smart Citations
“…The second study reported an adjusted OR of 259; 95% CI: −787 to 1306, P = 0.627 [25,26]. However, Abomhya et al (215 049 patients) demonstrated an increase in median total hospitalization costs of 32 305.5 USD; IQR = 18 600-61 599 in NAFLD+IBD patients vs. 30 782 USD; IQR = 16 847-58 667, P < 0.001 for those with IBD alone [18]. Noorian et al also showed increased cost of care (COC) in patients with IBD and NAFLD ranging from 7223 to 7634 USD; 95% CI: 923-17 116, P < 0.01 in CD (18 170 patients) and 8358 to 9392 USD; 95% CI: 3200-14 662, P < 0.01 in UC patients (9866 patients) [19].…”
Section: Hospitalization Costmentioning
confidence: 93%
“…33 [ 23,27], and an adjusted hazard ratio of 2.5; 95% CI: 1.3-4.9 [23,27], as reported in Table 2. The third study did not report hospitalization rates [18,19,[24][25][26].…”
Section: Hospitalization Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a retrospective cohort study of patients discharged with a diagnosis of CD between 2016 and 2018. The study was performed in accordance with the 1963 Helsinki Declaration and is exempt from an Institutional Review Board due to the lack of any identifying patient information [17,18].…”
Section: Data Source and Study Designmentioning
confidence: 99%